2021
DOI: 10.1515/nanoph-2021-0411
|View full text |Cite
|
Sign up to set email alerts
|

Multiple excitons dynamics of lead halide perovskite

Abstract: The lead halide perovskite material shows its unique photoelectric properties, the resulting conversion efficiency of perovskite solar cells. However, the efficiency comes to a bottleneck owing to that mechanism research fall behind the device research. Multiple excitons dynamics play an important role, especially in the lifetime and binding energy of multiple excitons. A long multiexciton lifetime is beneficial to the application for light-emitting devices and photovoltaic devices. Large multiexciton binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Hence, the fast time component of 3.57 ps is attributed to the cooling process of a hot STB . It has been reported that nonradiative Auger recombination of biexcitons widely exists in systems with strong quantum confinement effects, for example, perovskite quantum dots, leading to short lifetimes. ,, The reported biexciton lifetimes are ranging from 38 to 204.6 ps for lead halide perovskites . If the second time component of 64.98 ps is related with the Auger recombination of STBs, STBs will fast relax to the single STE state.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the fast time component of 3.57 ps is attributed to the cooling process of a hot STB . It has been reported that nonradiative Auger recombination of biexcitons widely exists in systems with strong quantum confinement effects, for example, perovskite quantum dots, leading to short lifetimes. ,, The reported biexciton lifetimes are ranging from 38 to 204.6 ps for lead halide perovskites . If the second time component of 64.98 ps is related with the Auger recombination of STBs, STBs will fast relax to the single STE state.…”
Section: Resultsmentioning
confidence: 99%
“…33 It has been reported that nonradiative Auger recombination of biexcitons widely exists in systems with strong quantum confinement effects, for example, perovskite quantum dots, leading to short lifetimes. 29,30,34 The reported biexciton lifetimes are ranging from 38 to 204.6 ps for lead halide perovskites. 34…”
Section: Ste Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrafast dynamics of excitons, trions, and biexcitons in LHP NCs can be investigated in detail by using femtosecond transient absorption spectroscopy and time-resolved PL spectroscopy. 61,[69][70][71][72][73][74][138][139][140][141][142][143][144] In transient absorption spectroscopy, excitons, trions, and biexcitons generated by a pump pulse can be measured via the change in the transmission of a probe pulse. As shown in Fig.…”
Section: Biexciton Recombination Dynamicsmentioning
confidence: 99%
“…Due to the special band structure of LHP NCs, biexcitons and multiexcitons often exist under its practical application conditions. It was reported that the carrier recombination and separation of LHP NCs are essential steps for developing efficient photovoltaic/optoelectronic devices . Therefore, a deep understanding of the biexcitons and/or multiexcitons dynamics of LHP NCs after light excitation is the key to better utilizing them and designing high-performance photo-driven devices.…”
Section: Introductionmentioning
confidence: 99%